Bibliometric Mapping of Research on Decentralization and Performance Evaluation - Rostini; Ergicho, Yisihak (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze trends, developments, and directions of scientific research related to decentralization and performance evaluation between 2015 and 2025. Using a bibliometric approach and data from the Scopus database, this study evaluates scientific publications based on the number of documents, country contributions, institutional affiliations, keywords, and collaborative networks between authors. The analysis shows that the number of publications fluctuates, with a significant spike in 2024. China is the country with the highest contribution to publications, while contributions from Indonesia remain very minimal. In terms of affiliations, Chinese universities dominate scientific production in this field. Network visualization shows that collaboration between researchers remains low and fragmented. The most dominant keywords are decentralization, blockchain, and performance evaluation, which form several research clusters that show links to financial management and public policy topics. These findings indicate the need to increase the involvement of Indonesian researchers and strengthen global collaborative networks on the topic of decentralization and performance evaluation.